Hierarchical super-regions and their applications to biological volume segmentation - Luengo, Imanol (2018)
Advances in Biological Imaging technology have made possible imaging of sub-cellular samples with an unprecedented resolution. By using Tomographic Reconstruction biological researchers can now obtain volumetric reconstructions for whole cells in near-native state using cryo-Soft X-ray Tomography or even smaller sub-cellular regions with cryo-Electron Tomography. These technologies allow for visualisation, exploration and analysis of very exciting biological samples, however, it doesn’t come without its challenges. Poor signal-to-noise ratio, low contrast and other sample preparation and re-construction artefacts make these 3D datasets to be a great challenge for the image processing and computer vision community. Without previous available annotations due to the biological relevance of the datasets (which makes them not being publicly available) and the scarce previous research in the field, (semi-)automatic segmentation of these datasets tends to fail.